A Novel Method for Solving Simultaneous Equations in Boolean/Switching Algebra - Bhattacharjee, Pramode Ranjan (IETE journal of education, 2018)
This paper reports on a novel method for finding the solution(s) of a set of simultaneous equations in Boolean/Switching algebra. It is based exclusively on the sets of minterms and maxterms of switching functions involved in the given set of simultaneous equations. That such a problem of generation of the solution(s) of simultaneous Boolean equations can be translated fully (when none of the given set of equations contains 0 or 1 on any one side) or partially (when at least one of the given set of equations contains 0 or 1 on any one side) to pseudo-Boolean programming has also been demonstrated by considering two examples.